Apresentação do dossiê "Lutas feministas e LGBTQ+ pela democracia no Brasil" - Pedro, Joana Maria; Ferreira Veras, Elias (Anos 90, 2020)
Apresentação do dossiê "Lutas feministas e LGBTQ+ pela democracia no Brasil"